Kant’s Sublime in Context: The Historical Sources and Impact of Kant’s notion of the Sublime - Giesbers, Tom (Con-Textos Kantianos. International Journal of Philosophy, 2026)
Kant’s sublime is a complicated concept because it occupies an often contested position in the final volume of Kant’s critical philosophy. Adding diachronically to the significant body of scholarship on the systematic significance of the sublime within Kant’s critical philosophy this paper aims to demonstrate the degree to which Kant’s sublime is inspired by a complicated set of historical antecedents. It reconstructs the sources that led Kant to the attributes of his sublime, strengthened by an overview of the attempts to modify this concept among Kant’s contemporaries. Ultimately this paper provides a historical vantage point for placing Kant in the history of the concept of the sublime that goes beyond established general historical overviews of the history of aesthetics, because it reconstructs the way in which Kant constructs and transforms the concept as well as the ways in which his contemporaries took his conception of the sublime to be significant.